Conceptual Framework of Energy-and-Ecology of Indoor Plant Lighting - Sergei A. Rakut’ko (Сельскохозяйственные машины и технологии, 2018)
Abstract. To increase the efficiency of horticulture, the technology of plant cultivation under artificial lighting, i.e. indoor plant lighting, is widely used. The author proposes to expand the range of issues considered in this field and highlight the energy-and-ecology of horticulture (EEH) as a scientific area located at the junction of power engineering and technical subjects, plant physiology, and ecology. (Research purpose) To develop a conceptual framework of the energy-and-ecology of horticulture. (Materials and methods) The object of EEH research is an artificial bioenergetic system of horticulture (ABSH), i.e. a combination of living organisms and technological equipment in a plant growing facility. A mathematical description of the regularities of transferring a substance in horticulture is produced on the basis of a hierarchical model of ABSH. The subject of the EEH study is the regularities of the transformation of matter and energy flows in ABSH. (Results and discussion) The author has determined some specific indicators of energy-ecological compatibility and obtained an expression for determining the energy-ecological coefficient of horticulture through its technological indicators. The paper offers an interpretation of the term "energy-and-ecology of horticulture" as a property of the technological process of plant growing in artificial conditions to meet the requirements of energy efficiency and environmental friendliness. It is shown that an approach based on the concept of best available technologies (BAT) can be applied to the indoor plant lighting. An expression for the quantitative assessment of the energy-ecological parameter in terms of the proximity of the development trajectories of ABSH in a state-space has been obtained. The author proposes an algorithm for BAT forming to be applied in indoor plant lighting. (Conclusions) For the first time, the author raises a question about the development of structural elements of the BAT formation algorithm in lighting horticulture in terms of energy-ecological indicators as an integrative optimality criterion of the system. The author has developed energy audit techniques to optimize the process of plant growing according to the criterion of minimal deviations of energy-ecological performance by varying the lighting parameters, environmental conditions and other factors. Complex implementation of energy- and ecological technologies of indoor plant lighting will allow increasing the efficiency of the production process, reducing the energy intensity while improving the quality of products and ensuring the environmental friendliness of production.